Acclimation of barley plants to elevated CO2 concentration and high light intensity does not increase their protection against drought, heat, and their combination - Hana Findurová; Otmar Urban; Barbora Veselá; Jakub Nezval; Radomír Pech; Vladimír Špunda; Karel Klem (Plant Stress)
Plants face fluctuations in environmental conditions throughout their life cycles. Some of these conditions, such as CO2 concentration and increasing temperature, are closely linked to ongoing climate change. These conditions not only affect plant growth and development but also modify the response to sudden exposure to stressors through morphological, physiological, and biochemical acclimation. Understanding these responses is therefore important for defining adaptation strategies for future crop production. In this study, we tested the acclimation effect of light intensity (low, high) and CO2 concentration (low, ambient, elevated) on barley plants and its implications for subsequent responses to drought, heat, and their combination. The acclimation to the growth conditions induced numerous changes both in plant morphology and physiology. The whole-plant leaf area was stimulated by increasing light intensity and CO2 concentration. That led to increased whole-plant transpiration despite the trend of stomatal conductance was the opposite in comparison to leaf area. The increased whole-plant transpiration then increased the sensitivity of barley plants to the stress treatments. Similarly, the stimulatory effect of high light intensity on antioxidative capacity was not sufficient to improve barley performance under the stress treatments. The presented results show that for physiological or biochemical indicators of stress tolerance to be realistically used to evaluate the expected response to stress conditions, they must be related to the morphology of the whole plant, which influences both the severity of stress and the quantitative role of resistance mechanisms.